DESAIN BREAKWATER SISI MIRING SEBAGAI UPAYA MENGANTISIPASI LIMPASAN AIR LAUT PADA BANGUNAN REVETMENT DI PANTAI MALABERO KOTA BENGKULU - Yannovita, Welendri; Besperi, Besperi; Gunawan, Gusta (Inersia: Jurnal Teknik Sipil, 2017)
This research aims to desaign of sideways breakwater as an effort to anticipate the water  overflow On The Revetment Building At Malabero Beach Bengkulu City. The data used is primary data and secondary data. Primary Data Processing Method Used in Field Direct Namely Collection (Hs and Ts), while the secondary data analysis method using wind data, analysis data tides and topography. The results of the breakwater have the elevation 0f 5,55m, width 3,71 m on the head and 3,91 m on the arms. Weight unit protective cover breakwater head W=3,31 tons, W/10=331 kg, W/200=16 kg and the arms W= 3,87tons,  W/10=387 kg,W/200= 19 kg. With 13 and 12 slides of cover in each 10 m on the head and arm.